On the Way Out: An Analysis of Patient Transfers from Four, Large-Scale, North American Music Festivals Over Two Years. Issue Volume 34:Issue s1(2019) (May 2019) - Callaghan, Christopher; Turris, Sheila; Rabb, Haddon; Munn, Brendan; Lund, Adam
Abstract : Introduction: Music festivals are globally attended events that bring together performers and fans for a defined period of time. These festivals often have onsite medical care to help reduce the impact on local healthcare systems. Historically, the literature suggests that patient transfers offsite are frequently related to complications of substance use. However, there is a gap in understanding as to why patients are transferred to a hospital when an onsite medical team, providing a higher level of care (HLC), is present. Aim: To better understand the causes that necessitate patient transportation to the hospital during festivals that have onsite physician-led coverage. Methods: De-identified patient data from a convenience sample of four, large-scale Canadian festivals (over two years) were extracted. Patient encounters that resulted in transfers to hospital, by ambulance, non-emergency transport vehicle (NETV), or self-transportation were analyzed for this study. Results: Each festival had an onsite medical team that included physicians, nurses, and paramedics. During 34 event days, there were 10, 406 patient encounters, resulting in 156 patients requiring transfer to a hospital. A patient presentation rate of 16.5/1, 000 was observed. The ambulance transfer rate was 0.12/1, 000 of attendees. The most common reason for transport was musculoskeletal injuries (54%) that required imaging. Discussion: The presence of onsite teams capable of treating and releasing patients impacted the case mix of patients transferred to a hospital, and may reduce the number of transfers for intoxication. Confounding preconceptions, patients in the present study were transferred largely for injuries that required imaging. Results suggest that a better understanding of the specific effects onsite medical teams have on avoiding off-site transfers will aid in improving planning for music festivals. Findings also identify areas for further improvement in care, such as onsite radiology, which could potentially further reduce the impact of music festivals on local health services.